‘Drugs, guns and gangs’: case studies on Pacific states and how they deploy NZ media regulators - Robie, D (Pacific Media Centre, Auckland University of Technology, 2012)
Media freedom and the capacity for investigative journalism have been steadily eroded in the South Pacific in the past five years in the wake of an entrenched coup and censorship in Fiji. The muzzling of the Fiji press, for decades one of the Pacific’s media trendsetters, has led to the emergence of a culture of self-censorship and a trend in some Pacific countries to harness New Zealand’s regulatory and self-regulatory media mechanisms to stifle unflattering reportage. The regulatory Broadcasting Standards Authority (BSA) and the self-regulatory NZ Press Council have made a total of four adjudications on complaints by both the Fiji military-backed regime and the Samoan government and in one case a NZ cabinet minister. The complaints have been twice against Fairfax New Zealand media—targeting a prominent regional print journalist with the first complaint in March 2008—and twice against television journalists, one of them against the highly rated current affairs programme Campbell Live. One complaint, over the reporting of Fiji, was made by NZ’s Rugby World Cup Minister. All but one of the complaints have been upheld by the regulatory/self-regulatory bodies. The one unsuccessful complaint is currently the subject of a High Court appeal by the Samoan Attorney-General’s Office and is over a television report that won the journalists concerned an investigative journalism award. This article examines case studies around this growing trend and explores the strategic impact on regional media and investigative journalism.
Keywords: Accountability; Censorship; Fiji; Fourth Estate; Investigative journalism; Media law; Ethics; Media regulation; Media self-regulation; Military regimes; Samoa